The Establishment of Thermodynamic Model for Ti Bearing Steel-Slag Reaction and Discuss - Zhao, Mao-Guo; Wang, Xu-Feng; Chen, Gu-Jun; He, Sheng-Ping (Frontiers in Materials, 2022)
A thermodynamic model for seven CaO-MgO-BaO-CaF2-SiO2-Al2O3-TiO2 ladle slags based on the Ion and Molecule Coexistence theory (IMCT) is establishment and validated by the experiment results at 1873K. The calculated activity of SiO2, Al2O3 and TiO2 in the slag can be approved by the experiment results and the IMCT model used in this study is reasonable. Then the influence factors such as the mass ratio of CaO to SiO2 (C/S ratio) ranging from 1 to 10, the mass ratio of CaO to Al2O3 (C/A ratio) ranging from 1 to 2.5, TiO2 content (wt pct) ranging from 0 to 30, BaO content(wt pct) ranging from 0 to 30 are investigated based on the thermodynamic calculating results. The raise of C/S ratio, TiO2 content and BaO content in the slag can increase the molar Gibbs energy change (ΔG) of Ti reacted with SiO2 and Al2O3 or Al reacted with SiO2. The effect of C/A ratio on the molar Gibbs energy change (ΔG) of Ti reacted with SiO2 and Al2O3 or Al reacted with SiO2 was less. Finally, the slag with higher C/S ratio and TiO2 content and appropriate BaO content can weaken the reaction between Ti and SiO2 or Al2O3 in the slag.